Autonomous and integrated parking and transportation services - Chatterjee, Amalendu (Telecommunications engineer) (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2020)
"In this book, the author outlines a Robust Web Parking, Truck and Transportation Portal (RWPTTP) for integrating parking and transportation services - a revolutionary approach in contrast to incremental change for managing traffic congestion. Autonomous vehicle technology, artificial intelligence, internet of things (IOT) and other interconnected hardware and software tools will assist autonomous parking and transportation services and provide next century infrastructure for consolidated transportation customer services. The book highlights currently available autonomous parking and transportation technologies, and the development of an integrated and intelligent transportation service/system (IITS) platform, with specific use of technologies to reconfigure the transportation industry. The author also suggests many regulatory and policy changes to simplify data collection, traffic operation, introduction of duplicate transportation system using light rails (LRs) and High Speed Rails (SPRs) and redistribution of parking spaces along such routes for using renewable energy"--
Thinking of a New Parking Paradigm -- Public Perception of the Current Parking Paradigm -- Emerging Technologies and Associated Terminologies -- RWPTTP Technical Design Outlines -- Single Payment Method -- Parking Space as a Source of Renewable Energy -- Enhancing IPMI Sustainability Framework -- Easing Parking Regulations -- Optimum Land Use & Pay-As-You-Use Smart Transportation -- Why a New Business Model?
OCLC-licensed vendor bibliographic record.
Keywords: Automobile parking; Transportation, Automotive; Automated vehicles; COMPUTERS / General; COMPUTERS / Computer Graphics / Game Programming & Design